(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Acne vulgaris is a common skin disease, which is a significant health problem among adolescents and young adults. It affects 85-100% of people at some point in their lives, and it usually begins at puberty. Acne can persist into the 30s and beyond. Objective: To evaluate the risk factors for development of acne vulgaris among Mosul University students in Mosul- Iraq. Methods: A case-control study conducted to 300 persons (150 cases and 150 controls) aged 18-35 years selected randomly among Mosul University students who attended university primary health care that located inside Mosul University, Iraq, during the sixth month period from august 2019 to January 2020. Results: Of the acne vulgaris cases (150 cases) that included in the study, 45 % are males and 55% are females, those with age group 18-23 years has 1.8 risk for developing of acne, always stress has 2.7 risk, female cases with irregular cycle have 58 times risk. 53% of female & 46% of male have acne on their face and male patients have 35 risk for acne on their shoulder, oily skin has 3 times risk, two and more members in family with acne have 4 risk followed by 3 times risk of one family member with acne, student’s mobile use has about 2 times risk for developing of acne. Conclusion: There were several significant factors associated with acne formation in the study, which play a role in acne formation including age, psychological status, menstrual cycle irregularity, site of appearance of acne, nature of the skin, family history, using student’s mobile. Keywords: Acne vulgaris, risk factors, university students Citation: Khaleel FF. Risk factors of acne vulgaris among Mosul University Students from Iraq. Iraqi JMS. 2022; 20(1): 51-58. doi: 10.22578/IJMS.20.1.7